The importance of Latin American space in the internationalization of Portuguese SMEs - Brás-dos-Santos, André (2020)
In the light of the transformation undergone in the last decade by the Portuguese economy, the internationalization of Portuguese companies through exports had a considerable growth, reducing the importance of domestic demand as the main variable in the contribution to GDP, this work addresses the role of SMEs in this process, analyzing the case of their internationalization to the Latin American space. The study is based on an empirical analysis of data resulting from a survey conducted in 2014, period where the transformation became clear, through the responses of 50 internationalized Portuguese SMEs to Latin America, which have been validated. Also, and with a focus on this research, the process was correlated with the relevant theories of internationalization, paving the way for more in-depth and methodologically based studies on this relationship with significant potential, but still little analyzed in the context of the Portuguese economy.